Implementasi Metode Analytical Hierarchy Process Pada Sistem Pendukung Keputusan Dalam Penentuan Pembelian Camera (Studi Kasus Digital Kamera) - Ahmad Riyadi; Dimas Abisono Punkastyo (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2023)
The camera is an electronic device that is widely used throughout the world, in the camera there are also specifications and criteria for the camera. the use of cameras in society that is most often used is to make money and hobbies. There are still many people who buy cameras without looking at the specifications or criteria of the camera, so that the camera used is not flexible and in accordance with what is desired. So a Camera Purchase Recommendation Decision Support System using the Analytical Hierarchy Process (AHP) method is needed to rank decision alternatives and choose the best one with several criteria, by developing a numerical value to rank each decision alternative based on the extent to which each alternative meets the decision maker's criteria. The result of this research is to reduce the risk of buyer error in choosing a camera with the criteria needed for decision making, it would be very suitable to use this method with multiple criteria, because it is able to choose the best alternative from a number of alternatives.